DEVELOPMENT OF PERFORMANCE APPRAISALS AS AN ALTERNATIVE TO MEASURING CRITICAL THINKING SKILLS IN ELEMENTARY MATHEMATICS LEARNING - Sarifah, Iva; M Kurnianti, Endang (IJBLE Scientific Publications Community Inc., 2023)
This study aims to produce a performance assessment instrument as an alternative to measure critical thinking skills in elementary mathematics learning. This study describes the process of developing assessment instruments and rubrics used to measure critical thinking skills in grade IV elementary school mathematics learning. This research was conducted in elementary schools in DKI Jakarta. The development of performance appraisal instruments as an alternative to measuring critical thinking skills in elementary mathematics learning is research and development (Research and Development / R &D) using mixed methods research. The model used in this study is the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). This research has just been carried out with the stages carried out in this study Analyze, Design, Development, and Implementation. Data collection using non-test techniques, namely interviews and product assessments. Data was analyzed using descriptive analysis techniques including expert judgment conducted by material experts (elementary mathematics learning), learning evaluation, and language. The calculation of validation results using Aiken's statistics and instrument reliability is inter-rater reliability calculated using the Hoyt variance technique. VProduct feasibility alidation in terms of material, construction, and language aspects. The results of the analysis show that all instrument items are valid with a reliability coefficient of 0.98. The feasibility test results showed that the average feasibility of material aspects was 86.7%; construction aspect by 92%; and the language aspect of 90.7% with an overall average of 89.8%. These results show that the performance assessment instrument as an alternative to measuring critical thinking skills in grade IV elementary mathematics learning is categorized as very feasible. Thus, this instrument can be used in grade IV elementary mathematics learning.